Realistic Mathematics Education Approach in Junior High School Mathematics Learning in Indonesia (2010-2024): A Bibliometric Analysis - Ningrum, Sri Adiningsih Utami; Slamet, Isnandar; Fitriana, Laila (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
RME is an approach to teaching that starts from things that are real for students. This is relevant to current education that focuses not only on academic knowledge but also on the development of relevant skills for the world of work and everyday life. The purpose of this article is to find out the research trends regarding the realistic approach to mathematics education in secondary school and to find out the research topics that have the potential to be used as research in the future. The method used in this research is bibliometric analysis. The research data was obtained through Harzing's Publish or Perish software with Google Scholar database, the keywords realistic mathematics education and junior high school, the maximum number of results is 1000 abstracts, and the keywords are written in English and Bahasa Indonesia. The articles obtained were 960 articles with a period of 2010-2024. Then, restricted to Scopus-accredited journals, Sinta 2, and Sinta 3; there are 99 articles were obtained. The results showed that the publication trend with the research theme of an RME approach experienced the highest increase between 2016-2018 and 2021-2023. In addition, the research theme of the RME approach, which has the opportunity to be used as research in the future, has two keywords, namely systematic literature review and reasoning.